Immunogenicity and Immune Silence in Human Cancer - Yarmarkovich, Mark; Farrel, Alvin; Sison, Artemio; di Marco, Moreno; Raman, Pichai; Parris, Joshua L.; Monos, Dimitrios; Lee, Hongzhe; Stevanovic, Stefan; Maris, John M. (Frontiers in Immunology, 2020)
Despite recent advances in cancer immunotherapy, the process of immunoediting early in tumorigenesis remains obscure. Here, we employ a mathematical model that utilizes the Cancer Genome Atlas (TCGA) data to elucidate the contribution of individual mutations and HLA alleles to the immunoediting process. We find that common cancer mutations including BRAF-V600E and KRAS-G12D are predicted to bind none of the common HLA alleles, and are thus “immunogenically silent” in the human population. We identify regions of proteins that are not presented by HLA at a population scale, coinciding with frequently mutated hotspots in cancer, and other protein regions broadly presented across the population in which few mutations occur. We also find that 9/29 common HLA alleles contribute disproportionately to the immunoediting of early oncogenic mutations. These data provide insights into immune evasion of common driver mutations and a molecular basis for the association of particular HLA genotypes with cancer susceptibility.